Semiotic Elements on William Shakespeare’s Hamlet Prince of Denmark - Atrinawati Atrinawati (Culturalistics: Journal of Cultural, Literary, and Linguistic Studies, 2018)
ABSTRACTThis article analysis Hamlet Prince of Denmark, a tragic drama written by William Shakespeare. The purpose of this study is to finding out basic narrative scheme, prime signifier and paradigmatic and syntagmatic aspects of the drama. The approaches that I used is semiotics and close reading. The result shows that the narration centered on a binary opposition, hesitated revenge being the prime signifier, and paradigmatic and syntagmatic revealed details of the signals. Based on the analyses, William Shakespeare’s Hamlet Prince of Denmark contain prime signifier Keywords: semiotic; signifier; paradigmatic; syntagmatic.